The Role of Female and Millennial Directors on the Environmental Performance of Indonesian SOEs - Wardhani, Dian Kusuma; Purwinanti, Eiffeliena Nur'aini; Priandi, Muhammad (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 17 No 2 (2022), 2022)
The Indonesian Ministry of SOEs seeks to increase the proportion of female and millennial directors on the SOE board of directors to improve the environmental performance of SOE. This study aims to obtain empirical evidence of female and millennial directors' influence on the environmental performance of SOE. The results indicate that female directors have a negative effect on environmental performance. The proportion of female directors is only a political reason to meet the quota requirements for women directors on the SOE board of directors. They only practice tokenism without having management power over the environment. Conversely, millennial directors have a positive impact on environmental performance. Robustness testing shows the same results as the primary research model and proves that this study's findings are robust. This research has implications for The Ministry of SOEs to increase millennial directors' representation to improve SOE corporate governance and obtain high environmental performance. Keywords : female directors, millennial directors, environmental performance